Coronary artery bypass grafting—fifty years of quality initiatives since Favaloro - Squiers, John J.; Mack, Michael J. (Annals of Cardiothoracic Surgery, 2018)
Coronary artery bypass grafting (CABG) remains one of the most commonly performed major surgical procedures worldwide and the most common procedure performed by cardiac surgeons. Rene Favaloro is widely credited with recognizing the true potential of CABG and subsequently popularizing the technique in a broad manner. Since the era of Favaloro in the late 1960s, the evolution of CABG can be understood through a series of quality initiatives that have defined which patients can benefit from the procedure and via which technique(s) they will derive the greatest benefit. Herein, we will review some of the key developments in CABG over the last 50 years with a focus on ongoing quality initiatives that will continue to refine the optimal applications and outcomes of CABG for the next 50 years.